Satisfaction and Trust Analysis Of Sipp Online BPJS Ketenagakerjaan Users: What Is The Role Of Ease of Use, Variations in Web Design and Functions? - Kuntadi Adi Setyawan; Usep Suhud; Agung Wahyu Handaru (LPPM Universitas Negeri Jakarta, 2020)
This study aims to review and reconfirm research on customer satisfaction and customer trust in online applications. In this study, the object raised is SIPP Online, developed by BPJS Ketenagakerjaan at the branch office of BPJS Ketenagakerjaan Kelapa Gading. This research model includes Customer Satisfaction, Customer Trust, Variation of Functions, and Web Design. Confirmatory Factor Analysis (CFA) to test the path analysis of Structural Equation Modeling (SEM) by operating the AMOS 22 application for testing research models. The sample in this study amounted to 315 PIC companies participating in BPJS Ketenagakerjaan. In this study, there are seven direct hypotheses and three indirect hypotheses (mediation). The results of this study indicate that all hypotheses made in the study are statistically accepted. The limitation in this research is that the study's scope only includes the Kelapa Gading branch of the BPJS Ketenagakerjaan.